Prevalence of dental anomalies in permanent dentition of Brazilian individuals with down syndrome - Cuogh, Osmar Aparecido [UNESP]; Topolski, Francielle [UNESP]; de Faria, Lorraine Perciliano [UNESP]; Occhiena, Carla Machado [UNESP]; Pinto Ferreira, Nancy Dos Santos [UNESP]; Ferlin, Camila Ribeiro [UNESP]; de Mendonça, Marcos Rogério [UNESP] (Bentham Science Publishers, 2016)
Objective: The aim of this study was to evaluate the incidence of dental anomalies in the permanent dentition of individuals with Down Syndrome (DS) to increase the knowledge on the dental issues in this syndrome. Method: One hundred and five panoramic X-rays of patients with DS (61 males and 44 females), aged 7 to 42 years were used. The data were statistically analyzed using bivariate analyses test (p <0.05). Results: Dental anomalies were observed in 50.47% of the sample. More than one anomaly was observed in 9.52% of the individuals. The most frequent dental anomalies were hypodontia and microdontia (16.19%), followed by retained tooth (10.47%), taurodontism (9.52%), supernumerary teeth (5.71%), macrodontia (2.85%) and root dilaceration (0.95%). There was no statistically significant difference between genders for any of the anomalies. Conclusion: A high prevalence of dental anomalies was observed in individuals with DS. The results of the present study reinforce the importance of good dental care, offering a greater basis for professionals who provide dental service to these patients.
Keywords: Dental care; Disabled persons; Down syndrome; Panoramic radiograph; Permanent dentition; Tooth anomalies